INSIDER TRADING IN INDIA - RULES TILL NOW - Bali, Reema (International Journal of Research -GRANTHAALAYAH, 2020)
This paper analyses the lose threads amongst the SEBI (“Securities and Exchange Board of India”) as a regulatory authority (“regulator”) who are required enforce the laws and reforms to efface insider trading in the Indian economy. The paper focuses on the role of regulatory authority dealing with the cases of insider trading and the elements that might lead to delay in the resolving the matters which leads to piling up of unresolved matters in insider trading leading to disturbing the economy and loss of faith of investors on the trading activities of stock market.